Can the Accuracy of Home Blood Glucose Monitors be affected by the Received Signal Strength of 900 MHz GSM Mobile Phones? - Eslami J.; Ghafaripour F.; Mortazavi S. A. R.; Mortazavi S. M. J.; Shojaei-fard M. B. (Journal of Biomedical Physics and Engineering, 2015)
Background: People who use home blood glucose monitors may use their mobile phones in the close vicinity of medical devices. This study is aimed at investigating the effect of the signal strength of 900 MHz GSM mobile phones on the accuracy of home blood glucose monitors. Methods: Sixty non-diabetic volunteer individuals aged 21 - 28 years participated in this study. Blood samples were analyzed for glucose level by using a common blood glucose monitoring system. Each blood sample was analyzed twice, within ten minutes in presence and absence of electromagnetic fields generated by a common GSM mobile phone during ringing. Blood samples were divided into 3 groups of 20 samples each. Group 1: exposure to mobile phone radiation with weak signal strength. Group2: exposure to mobile phone radiation with strong signal strength. Group3: exposure to a switched–on mobile phone with no signal strength. Results: The magnitude of the changes in the first, second and third group between glucose levels of two measurements (׀ΔC׀ (were 7.4±3.9 mg/dl, 10.2±4.5 mg/ dl, 8.7±8.4 mg/dl respectively. The difference in the magnitude of the changes between the 1st and the 3rd groups was not statistically significant. Furthermore, the difference in the magnitude of the changes between the 2nd and the 3rd groups was not statistically significant. Conclusion: Findings of this study showed that the signal strength of 900 MHz GSM mobile phones cannot play a significant role in changing the accuracy of home blood glucose monitors.